Modeling Volume-Speed-Density Relationship on the Cibubur Transyogi Road Based on Traffic Behavior During Peak Hours Activity - Juang Akbardin; Dadang Mohamad; A. Z. Rahmadani (GoAcademica Research & Publishing, 2023)
Transyogi road Cibubur is the main road connecting the activity zone in the city of Bogor. This research models the Volume - speed - density relationship model to determine traffic behavior caused by the activity system in that zone. The research methodology used is quantitative descriptive research modeled using mathematical equations. The inter-city traffic movement that occurs on this section causes the traffic flow situation to become unstable, plus the large rate of increase in traffic and the number of vehicles in the area means it is necessary to carry out planning to anticipate future traffic movement needs. A macroscopic approach can show overall traffic flow. This approach is described by 3 parameters, namely traffic flow (volume), density and speed. The Greenshield, Greenberg, and Underwood models can describe the relationship mathematically between these three parameters. The results of the research show that the flow characteristics at peak hour conditions are shown in the Underwood model with the model significance analysis value on Friday having a value of 0.940. For the model equation between Speed and Density we get S = 54.1 Exp (–D/370.15) Volume and Density get V = 54.1 D Exp (–D/370.15) Volume and Speed get V = 370.15 S Ln (54.1/S). The volume - speed - density relationship model shows that traffic in urban areas has characteristics determined by the zones built from the cover area. So, controlling traffic volume during peak hours in this zone must be controlled by adjusting the activity system on the road corridors that are traversed.